2007
DOI: 10.1155/2007/29821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methamphetamine on Single Unit Activity in Rat Medial Prefrontal Cortex In Vivo

Abstract: To investigate how neuronal activity in the prefrontal cortex changes in an animal model of schizophrenia, we recorded single unit activity in the medial prefrontal cortex of urethane-anesthetized and awake rats following methamphetamine (MA) administration. Systemic MA injection (4 mg/kg, IP) induced inconsistent changes, that is, both enhancement and reduction, in unit discharge rate, with a subset of neurons transiently (<30 min) elevating their activities. The direction of firing rate change was poorly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Furthermore, a single MA injection evoked a robust decrease in neural firing, which is consistent with previous studies using high doses of psychostimulants in either anesthetized or awake-behaving animals (Gulley and Stanis 2010; Homayoun and Moghaddam 2006; Jang et al 2007). In the current study, no differences in baseline firing following sensitization were observed, which may be attributable to less exposure to the drug or the non-contingent route of administration.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a single MA injection evoked a robust decrease in neural firing, which is consistent with previous studies using high doses of psychostimulants in either anesthetized or awake-behaving animals (Gulley and Stanis 2010; Homayoun and Moghaddam 2006; Jang et al 2007). In the current study, no differences in baseline firing following sensitization were observed, which may be attributable to less exposure to the drug or the non-contingent route of administration.…”
Section: Discussionsupporting
confidence: 91%
“…Concerns about the neurotoxicity of methamphetamine following repeated administration are very well documented 26 43, 44 .Methamphetamine has been shown to induce toxicity in vivo and in vitro 26 affecting in particular, but not only, dopaminergic neurons 45 . Many studies have shown that the psychological and neurotoxic effects are related to dopamine release 9,46,47 although the molecular and cellular mechanisms involved in this process remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%